2013
DOI: 10.1073/pnas.1309781110
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed inhibitor targeting antigen-trimming aminopeptidases enhances antigen presentation and cytotoxic T-cell responses

Abstract: Intracellular aminopeptidases endoplasmic reticulum aminopeptidases 1 and 2 (ERAP1 and ERAP2), and as well as insulin-regulated aminopeptidase (IRAP) process antigenic epitope precursors for loading onto MHC class I molecules and regulate the adaptive immune response. Their activity greatly affects the antigenic peptide repertoire presented to cytotoxic T lymphocytes and as a result can regulate cytotoxic cellular responses contributing to autoimmunity or immune evasion by viruses and cancer cells. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
181
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 122 publications
(194 citation statements)
references
References 45 publications
(68 reference statements)
9
181
0
4
Order By: Relevance
“…8 The V max of the reaction was unaffected by the presence of the inhibitor, whereas K M was increased according to the expected inhibition, indicating that thimerosal acts as a competitive inhibitor of ERAP1 ( Figure 4A,B).…”
Section: E Ndoplasmic Reticulum (Er) Aminopeptidases Generatementioning
confidence: 82%
See 1 more Smart Citation
“…8 The V max of the reaction was unaffected by the presence of the inhibitor, whereas K M was increased according to the expected inhibition, indicating that thimerosal acts as a competitive inhibitor of ERAP1 ( Figure 4A,B).…”
Section: E Ndoplasmic Reticulum (Er) Aminopeptidases Generatementioning
confidence: 82%
“…8,9 In an effort to discover novel, nonpeptidic scaffolds that inhibit ERAP1 as leads for preclinical development we applied a combination of structure-based, ligand-based, and knowledge-based virtual screening approaches, taking advantage of key structural characteristics revealed in the recent crystal structures of ERAP1 and ERAP2 and their complexes with 1 and 2, respectively. 8,10,11 Toward this goal, we compiled a library of more than 265,000 compounds from selected collections of chemical vendors that are focused on drug-likeness and structural diversity (Table S1). The library was enriched with the National Cancer Institute's diversity set II (1364 compounds) and the DrugBank database comprising 6590 FDA-approved and experimental small-molecule drugs 12 We also performed a 3D pharmacophore search against the purchasable subset of the ZINC database (more than 20 million compounds) 13 using the online interface of ZINCPharmer.…”
Section: E Ndoplasmic Reticulum (Er) Aminopeptidases Generatementioning
confidence: 99%
“…In a similar way, Stratikos et al [84] reported the synthesis of the phosphinic tripeptide (R,S,S)-94, which was tested in the inhibition of the endoplasmic reticulum aminopeptidases 1 and 2 (ERAP1 and ERAP2), involved in regulation of cytotoxic cellular responses. Thus, the reaction of N-Boc H-phosphinic acid analogue of homophenylalanine (R)-92 [72] with HMDS followed by the addition of ethyl isobutylacrylate and saponification of the ethyl ester, gave the C-phosphinate 93 in 72% yield, which by coupling with (S)-TrpNH2, deprotection and HPLC separation, afforded the phosphinic tripeptide (R,S,S)-94 in 87% (Scheme 39) [78].…”
Section: Scheme 32 Synthesis Of the C-phosphinic Acid 75 And Its Actmentioning
confidence: 99%
“…In a similar way, Stratikos et al [84] reported the synthesis of the phosphinic tripeptide (R,S,S)-94, which was tested in the inhibition of the endoplasmic reticulum aminopeptidases 1 and 2 (ERAP1 and ERAP2), involved in regulation of cytotoxic cellular responses. Thus, the reaction of N-Boc H-phosphinic acid analogue of homophenylalanine (R)-92 [72] with HMDS followed by the addition of ethyl isobutylacrylate and saponification of the ethyl ester, gave the C-phosphinate 93 in 72% yield, which by coupling with (S)-TrpNH2, deprotection and HPLC separation, afforded the Considering that phosphinic peptides are well recognized as peptide isosters and powerful inhibitors of many classes of enzymes, mainly zinc proteases, Yiotakis et al [81,82] reported the synthesis of phosphinopeptidic building blocks incorporating a triple bond, which through 1,3-dipolar cycloaddition process, gives access to novel class of isoxazole-containing phosphinic peptides.…”
Section: Scheme 32 Synthesis Of the C-phosphinic Acid 75 And Its Actmentioning
confidence: 99%
See 1 more Smart Citation